2016
DOI: 10.1039/c6cc04661d
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-assisted, biocatalytic formate synthesis from CO2 and water using silicon-based photoelectrochemical cells

Abstract: We report on a silicon-based photoelectrochemical cell that integrates a formate dehydrogenase from Thiobacillus sp. (TsFDH) to convert CO2 to formate using water as an electron donor under visible light irradiation and an applied bias. Our current study suggests that the deliberate integration of biocatalysis to a light-harvesting platform could provide an opportunity to synthesize valuable chemicals with the use of earth-abundant materials and sustainable resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
0
29
0
3
Order By: Relevance
“…In many studies for photochemical regeneration of cofactors,o rganic sacrificial electron donors have been used to compensate electron supply.W hile the use of water molecules as electron donor is desirable for developing as ustainable photobiocatalytic process,i ti ss till challenging due to the difficulties in kinetic coupling between water oxidation and enzymatic reduction reactions. [82,139,140] Recently,a ni ntegral coupling of water oxidation and nicotinamide cofactor reduction was attempted by constructing at andem reaction chain of H 2 O( electron donor)-[Co 4 (H 2 O) 2 (PW 9 O 34 ) 2 ] 10À (water oxidation catalyst)-[Ru-(bpy) 3 ] 2+ (photosensitizer)-[Cp*Rh(4,4'-dcbpy)H 2 O] 2+ (electron mediator)-NAD + . [139] Theh omogeneous colloidal system regenerated only 10.7 %o fN ADH in 2h when coupled with water oxidation, which is approximately seven times lower than the yield achieved with TEOAasanelectron donor.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…In many studies for photochemical regeneration of cofactors,o rganic sacrificial electron donors have been used to compensate electron supply.W hile the use of water molecules as electron donor is desirable for developing as ustainable photobiocatalytic process,i ti ss till challenging due to the difficulties in kinetic coupling between water oxidation and enzymatic reduction reactions. [82,139,140] Recently,a ni ntegral coupling of water oxidation and nicotinamide cofactor reduction was attempted by constructing at andem reaction chain of H 2 O( electron donor)-[Co 4 (H 2 O) 2 (PW 9 O 34 ) 2 ] 10À (water oxidation catalyst)-[Ru-(bpy) 3 ] 2+ (photosensitizer)-[Cp*Rh(4,4'-dcbpy)H 2 O] 2+ (electron mediator)-NAD + . [139] Theh omogeneous colloidal system regenerated only 10.7 %o fN ADH in 2h when coupled with water oxidation, which is approximately seven times lower than the yield achieved with TEOAasanelectron donor.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Form ore efficient utilization of solar energy,Z -schemebased biocatalytic PECs were developed, involving dual illumination on both anode and cathode through mimicking the two-step photoexcitation scheme of natural photosystems. [54,140,157,158] Forexample,Son et al reported aZ-schemebased NADH photoregeneration system that consisted of CoPi-deposited, npp + triple-junction silicon on ITOg lass (3jn-Si/ITO/CoPi)a saphotoanode and hydrogen-terminated SiNWs as ap hotocathode. [140] The3 -jn-Si/ITO/CoPi photoanode oxidized water upon visible light irradiation, which was coupled with the transfer of hydrides to NAD + via an Rhbased mediator at the hydrogen-terminated SiNW photocathode.T he Z-scheme PEC system successfully reduced NAD + to NADH at ar ate of 0.064 mm h À1 under an applied voltage of 1.8 V. In the presence of FDH in the photocathodic compartment, 0.26 mm formate was produced after 6h reaction.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…For the first two requirements, a photoelectrochemical cell (PEC) configured with photoelectrodes can be a desirable option because it can deliver photoexcited electrons through an external wire to minimize back electron transfer . For light‐driven electrochemical water oxidation, n‐type bismuth vanadate (BiVO 4 ) has been regarded as a top‐performer photoanode material among other semiconductors .…”
Section: Introductionmentioning
confidence: 99%
“…[82,139,140] Kürzlich wurden Versuche zur Kopplung einer Wasseroxidation an die Reduktion von Nikotinamid-Kofaktoren mittels der Tandem [139] Das homogene,k ol-loidale System war bei Kopplung an die Wasseroxidation innerhalb einer Reaktionszeit von 2hnur in der Lage,1 0.7 % des NADH zu regenerieren und lieferte damit eine um etwa das siebenfache geringere Ausbeute als unter Einsatz von TEOAals Elektronendonor.Die Gesamtaktivitätvon mittels Wasseroxidation angetriebenen biokatalytischen Reduktionen wird durch einander entgegengesetzte Oxidations-und Reduktionsreaktion beeinträchtigt, die mit dem Rücktransfer von Elektronen und der Rekombination von Ladungen einhergehen. Die Nutzung von Wassermolekülen als Elektronendonoren ist unter dem Aspekt der Nachhaltigkeit photobiokatalytischer Prozesse von großem Interesse.S ie bleibt bisher allerdings aufgrund der Schwierigkeiten bei der kinetischen Kopplung der Wasseroxidation an enzymatische Reduktionsreaktionen eine Herausforderung.…”
Section: Nitrogenasenunclassified
“…[54,140,157,158] So berichteten beispielsweise Son et al von einem dem Z-Schema nachempfundenen NADH-Photoregenerationssystem bestehend aus einer Photoanode aus npp + -Triple-Junction-Silizium auf ITO-Glas mit darin inkorporiertem CoPi (3-jn-Si/ITO/CoPi)u nd wasserstoffterminierten SiNWs als Photokathode. Darin werden sowohl die Anode als auch die Kathode mit sichtbarem Licht bestrahlt und so das zweistufige Photoanregungsschema natürlicher Photosysteme nachgebildet.…”
Section: Kopplung Von Photobiokatalytischer Co 2 -Reduktion Und Nadh-unclassified